2018
DOI: 10.15557/jou.2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of spleen ultrasound elastography – a review

Abstract: In the last few years, notable technical progress has taken place in ultrasound elastography. Qualitative methods have been replaced by quantitative ones, such as: transient elastography, acoustic radiation force impulse and shear wave elastography. Owing to the fact that the spleen is superficially located, it is possible to obtain reliable measuring accuracy of its hardness using sonoelastography. Lately, many researchers have been investigating how spleen elasticity changes in patients infected with hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 41 publications
(87 reference statements)
1
19
0
2
Order By: Relevance
“…It is advisable that the patients hold their breath. This might not be possible in small children; however studies have shown that valid results can be obtained also with free breathing [58]. Convex or linear US probes can be used; the convex probes show higher variability [58,59].…”
Section: Spleenmentioning
confidence: 99%
See 2 more Smart Citations
“…It is advisable that the patients hold their breath. This might not be possible in small children; however studies have shown that valid results can be obtained also with free breathing [58]. Convex or linear US probes can be used; the convex probes show higher variability [58,59].…”
Section: Spleenmentioning
confidence: 99%
“…The normal values for children using pSWE (VTQ) are around 2.25 m/s [60]. Also, the size of the spleen has an influence on the stiffness values [58,61]. Obesity may reduce the quality of the B-mode US image, but this has not yet been investigated in studies.…”
Section: Spleenmentioning
confidence: 99%
See 1 more Smart Citation
“…Spleen stiffness measurement (SSM) with the same machine is accurate at predicting portal hypertension and esophageal varices . An SSM cutoff value of <41.3 kPa is highly sensitive (98%) at ruling out varices.…”
mentioning
confidence: 99%
“…а с другой -осведомленность врачей, как общей практики -семейной медицины, так и узких специальностей о его возможностях и критериях, продолжает оставаться довольно низкой [1,2,4,[6][7][16][17][18] . В свою очередь, среди органов, которые исследуются при ультразву-ке, весьма незначительную роль уделяют селезенке, диагностика заболеваний которой вообще является часто весьма отсроченной, что обусловлено, в первую очередь, низкой осведомленностью докторов о патологии данного органа вообще [3,5,[8][9][10][11][12][13][14][15] . Принимая это во внимание, целью данной работы является комплексный анализ возможностей ультразвукового исследования селезенки в норме и патологии .…”
unclassified